Manajemen Strategik dan Boarding School dalam Meningkatkan Mutu Pendidikan Pondok Pesantren - Ahyar Rasidi (LP2M STIT Palapa Nusantara, 2022)
Quality education can be implemented if the madrasah applies strategic management and good boarding schools. Moving on from these assumptions and the problem of weak madrasa management today, the authors are interested in conducting research with the aim of describing and analyzing profiles, implementing and evaluating strategic management and boarding schools in improving the quality of education. This research is a descriptive qualitative research method and the type of research is a case study conducted at MA Syaikh Zainuddin NW Anjani where the subjects of the research are the head of the madrasa, deputy head of the madrasa, treasurer, education staff, madrasa committee and teachers. Data collection techniques were carried out through observation, interviews and documentation studies. The results showed that the profile of MA Sheikh Zainuddin NW Anjani described the vision, mission, goals, objectives and profile of madrasa resources. Strategic management and boarding schools at MA Syaikh Zainuddin NW Anjani are carried out through madrasa internal and external environmental activities which are described through the madrasa organizational structure, teamwork and division of madrasa tasks, study days and times, financing assets, curriculum, madrasa promotion, new student admissions, culture madrasas, code of ethics, madrasa policies, geographical, demographic, cultural environment and community appreciation, government regulations, developments in science and technology, involvement of madrasa committees, partner institutions, alumni and strategic management and boarding schools in an effort to meet national education standards. The evaluation at MA Syaikh Zainuddin NW Anajani is carried out continuously involving top management and all madrasa personnel both short, medium and long term through madrasah self-evaluation instruments, teachers and benchmarking to improve madrasa performance and education quality.